Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Ax + b = 3x -3a
Ax- 3x = -(3a+b)
x(A-3) = - (3a+b)
x = - (3a+b) / (A-3)
Ax- 3x = -(3a+b)
x(A-3) = - (3a+b)
x = - (3a+b) / (A-3)
Apply the distributive property.
ax+b=3(x)+3(−a)
Multiply 3 by x to get 3x.
ax+b=3x+3(−a)
Move −1.
ax+b=−1⋅3a
Multiply −1 by 3 to get −3.
ax+b=−3a
Replace back in to larger expression.
ax+b=3x−3a
Since 3x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 3x from both sides.
ax+b−3x=−3a
Factor out the GCF of x from each term in the polynomial.
x(a)+x(−3)=−b−3a
Factor out the GCF of x from ax−3x.
x(a−3)=−b−3a
Divide each term in the equation by (a−3).
x=−3a+b/a−3
Answer:
x=−3a+b/a−3
ax+b=3(x)+3(−a)
Multiply 3 by x to get 3x.
ax+b=3x+3(−a)
Move −1.
ax+b=−1⋅3a
Multiply −1 by 3 to get −3.
ax+b=−3a
Replace back in to larger expression.
ax+b=3x−3a
Since 3x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 3x from both sides.
ax+b−3x=−3a
Factor out the GCF of x from each term in the polynomial.
x(a)+x(−3)=−b−3a
Factor out the GCF of x from ax−3x.
x(a−3)=−b−3a
Divide each term in the equation by (a−3).
x=−3a+b/a−3
Answer:
x=−3a+b/a−3
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.